The The Impacts of Preservice English Teachers’ Self-efficacy of Using AI Towards Their Intentions of Teaching Writing Skills Using AI - Putu Maha Surya Suardewa; I Putu Indra Kusuma; Kadek Sintya Dewi (Universitas Pendidikan Ganesha, 2024)
The use of artificial intelligence (AI) in the classroom is growing, particularly when it comes to writing instruction. However, because of their low self-efficacy, a lot of pre-service English teachers are reluctant to apply AI. This study aims to analyze how pre-service English teachers' intentions to teach writing with AI are influenced by their level of self-efficacy in the field. In this quantitative study, 303 aspiring English instructors at an public institution were surveyed. Researchers created two questionnaires to gauge behavioral intentions and self-efficacy. Simple Linear Regression was used to evaluate the results. Based on the research findings, self-efficacy significantly influences the intention to employ AI to teach writing skills. Teachers are more likely to use AI if they feel confident in using it. This study concludes that increasing self-efficacy in AI among pre-service teachers has a positive impact on their intention to integrate AI into teaching practice. These findings underscore the need for teacher training programs and educational institutions to focus on building confidence in using AI, which can improve teaching practices.